2022
DOI: 10.3390/diagnostics12081897
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Construct Validity of the Yale Pharyngeal Residue Severity Rating Scale: Performance on Videos and Effect of Bolus Consistency

Abstract: The Yale Pharyngeal Residue Severity Rating Scale (YPRSRS) provides an image-based assessment of pharyngeal residue in the fiberoptic endoscopic evaluation of swallowing (FEES). Its performance was investigated only in FEES frames. This study analyzed the reliability and construct validity of the YPRSRS in FEES videos and the influence of bolus consistency. Thirty pairs of FEES videos and frames, 8 thin liquids (<50 mPa·s), 11 pureed (2583.3 mPa·s at 50 s−1, 697.87 mPa·s at 300 s−1), and 11 solid food; were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…However, a recent study based on YPRSRS recognised the substantial complexity in rating PR on videos rather than on frames. The study demonstrated a trend of lower psychometric properties for videos, in comparison to an almost perfect agreement for frames 25 . Third, the “best-of-the-best” criterion adopted for the selection of the final images pool denoted a limitation, as it is not representative of common clinical practice.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, a recent study based on YPRSRS recognised the substantial complexity in rating PR on videos rather than on frames. The study demonstrated a trend of lower psychometric properties for videos, in comparison to an almost perfect agreement for frames 25 . Third, the “best-of-the-best” criterion adopted for the selection of the final images pool denoted a limitation, as it is not representative of common clinical practice.…”
Section: Discussionmentioning
confidence: 76%
“…Fourth, three different consistencies were randomly used in the study, which on one hand represents only a part of boluses available for FEES 21 , and on the other this might have lowered agreement results. In fact, it has been recently demonstrated that bolus consistencies play a role in determining the psychometric properties of the YPRSRS, with thin liquids (IDDSI 0) having the lowest levels of rating agreement than solid food (IDDSI 7) and pureed food (IDDSI 4), respectively 25 . Specific analysis for each consistency rated with the IT-YPRSRS and its clinical correlation is desirable in future research to better target rehabilitative interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative assessments comprised FEES with two validated scales: PAS (Rosenbek, 1996) (range from 1 normal to 8 severe) and the Yale Pharyngeal Residue Severity Rating Scale (YPRSRC) (Neubauer et al., 2015) (range from 1 none to 5 severe) (Rocca et al 2022) (0–5). FEES assessment involved food trials.…”
Section: Methodsmentioning
confidence: 99%